Competitive Performance Is Affected By A Competitive Strategy With Supply Chain Moderates - Herlin Rosalina Febriyanti Herlin; Elva Nuraina Elva; Nur Wahyuning Sulistyowati Nur (Ilomata International Journal of Tax and Accounting, 2020)
This study aims to examine the effect of competitive strategies on company performance with supply chains as moderating. This type of research is quantitative research. The sampling technique was purposive sampling. Data analysis techniques used simple linear regression and subgroups using Moderated Regression Analysis. The results of the study show that competitive strategies have an effect on company performance. Supply chain as a moderating variable strengthens the relationship of competitive strategies to company performance. Low cost strategies and differentiation are used in measuring competitive strategies. Where differentiation strategies are more applied than low cost strategies due to the object of research in the fields of property, real estate, building construction that produces limited and unique products at high costs.